Performance Test of Household Plastic Waste Shredding Machine - Lede, Agustinus Syrillus Umbu; Jafri, Muhamad; Gusnawati, Gusnawati (TURBO [Tulisan Riset Berbasis Online], 2024)
The abundance of plastic in daily life has a serious environmental impact as it takes 50-100 years to decompose. To solve this problem, plastic shredding machines are used to cut plastic waste into recyclable flakes. This study aims to determine the performance of plastic waste shredding machines. The method used is an experiment by testing the performance of the shredding machine at 1000 rpm, 1200 rpm, and 1400 rpm, with variations in the types of plastic waste Polyethylene (PE), Polypropylene (PP), and Polyethylene Tereftalat (PET). The observed parameters include engine production capacity, weight loss, and fuel consumption. The results showed that the production capacity of the machine increased as the rotation speed increased, with more efficient fuel consumption at higher rotation due to faster shredding time. A rotation speed of 1200 rpm produced more uniform shredding of PE and PET plastics, while the harder PP plastics required a speed of 1400 rpm for uniform results.